Study of the particles deformation of nickel coatings obtained by the cold gas-dynamic low pressure spraying technology - Каналес, Орасио; Шоринов, Александр Владимирович; Волков, Андрей Олегович; Маркович, Сергей Евгеньевич; Долматов, Анатолий Иванович (Technology audit and production reserves, 2015)
Deformation of the nickel particles during collision of the base surface with cold gas-dynamic spraying at different operating temperatures is studied in the article. The aim of this work is to determine the dynamic yield stress, temperature and plastic work of the particles in the cold spray. Nickel powder coatings on cold spraying device DYMET 405 were covered and the coating microstructure for measuring equivalent strain of the particles for each sample was analyzed to accomplish this aim. It is shown mathematical model to determine deformation parameters, for which one of the data source is founded equivalent deformation of the particles. This article presents the dynamic yield stress of the deformed particles, the calculated temperature in the contact area and the energy balance, with particular attention to the plastic particles. The calculations do not take into account the size of the particles and the deformation of the particles is considered equivalent to the entire coating. The presented method can be applied to studies of any coatings obtained by cold spraying. It can also be used to understand the influence of the parameters on the deposition of the coatings. In this paper it was established a high probability of melting of the particles and the effect of tamping by the ceramic particles of the metal particles to form a coating.